Characterization of interconnectivity of gelatin methacrylate hydrogels using photoacoustic imaging. Issue 4 (13th January 2022) - Zhao, Wenxiu; Yu, Haibo; Ge, Zhixing; Wang, Xiaoduo; Zhang, Yuzhao; Wen, Yangdong; Luo, Hao; Liu, Lianqing; Li, Wen Jung
Abstract : We developed a photoacoustic (PA) method for noninvasively characterizing the interconnection of porous hydrogels. Abstract : Hydrogels can provide a three-dimensional microenvironment for cells and thus serve as an extracellular matrix in a biofabrication process. The properties of hydrogels, such as their porosity and mechanical properties, significantly influence the cell growth. However, there is still a lack of effective methods for characterizing the hydrogel structure noninvasively. Herein, a photoacoustic (PA) imaging-based method is proposed for the characterization of gelatin methacrylate (GelMA) hydrogels. Owing to their high PA contrast, red blood cells (RBCs) are included as mediators in the GelMA hydrogel to analyze its pore distribution. The interconnectivity of the pores is further analyzed through the lysis of RBCs. The diffusion of the RBC lysis buffer in the GelMA is consistent with the trend observed in simulations. The analyzed vitality of HEK293 cells in different GelMA hydrogels reveals that understanding the diffusion of solutes ( i.e., nutrients) is a potential strategy to optimize the hydrogel parameters during biofabrication.